Perspektif Hukum Pidana Islam Terhadap Tanggung Jawab Pemilik Ternak - Harahap, Ain Zahrona; Habibi, Habibi; Harahap, Risalan Basri (Jurnal El-Thawalib, 2024)
The problem in this study is the responsibility of livestock owners for damage caused by their livestock, in (Sobar Village, Padang Bolak Julu District). Basically, everyone who owns and maintains livestock has full rights and obligations towards their livestock, for the damage caused by these livestock. In the case of damage caused by livestock, the owner of the livestock is obliged to provide compensation to the aggrieved party. This is in accordance with the positive law contained in article 1368 of the Civil Code and in Islamic law contained in surah Al-Baqarah verse 205 and the same is the case with the Perdes village of Sobar. The research method used is field research with a qualitative approach. Data sources consist of primary data, namely the Sobar village community and village officials, while secondary data, namely laws and journals related to the problems discussed in this study. Data collection techniques using interviews and documentation with qualitative descriptive data analysis techniques. The results of the study show that the responsibility of the livestock owner to the injured person is obligatory to compensate based on the agreed rules, but if livestock enter/damage the land but there is no responsibility for the livestock owner, then the land owner has the right to the livestock, because it is compensation from livestock that damage the land. However, in terms of compensation, there are obstacles that are often encountered, namely it is not known for sure who owned the livestock that caused the damage, there is no recognition from livestock owners because they are afraid of compensation. What can be done by landowners to be held accountable for losses caused by livestock through village officials so that they are more assertive in implementing applicable regulations, and specifically make identification marks for each livestock.